MWCNT activation and its influence on the catalytic performance of Pt/MWCNT catalysts for selective hydrogenation - A. Solhy (2008)
Multi-walled carbon nanotubes were submitted to three activation procedures: nitric acid oxidation, ball-milling and air oxidation. The influence of these treatments on nanotubes surface chemistry and morphology was evaluated by XPS, Raman and infrared spectroscopy, TGA, TPD, nitrogen adsorption and TEM. The three activated materials were used to prepare Pt supported catalysts from the organometallic precursor [Pt(CH3)(2)(COD)]. The influence of the activation treatments, together with that of a post-reduction thermal treatment, on the performances of the catalytic systems in the selective hydrogenation of cinnamaldehyde was investigated. It was shown that the best compromise between catalyst activity and selectivity requires a low amount of oxygenated groups on the support surface of the final catalyst, typically less than 700 mu mol/g CO + CO2 evolved during TPD experiments, together with an optimized platinum particle size ranging between 10 and 20 nm.